Safety and Efficacy of Anticoagulants - Rizzo, Toni (MD Conference Express, 2012)
Apixaban is an oral factor Xa inhibitor with prompt onset and offset of anticoagulation, twice-a-day dosing, and no need for coagulation monitoring. This article discusses the efficacy and safety of apixaban compared with warfarin in ARISTOTLE trial, and with aspirin in AVERROES Trial. This article also discusses the challenge of choosing anticoagulation therapy for patients with AF using the RE-LY, ROCKET, ARISTOTLE, and ENGAGE AF-TIMI 48 as examples.